Heart Failure and Cancer: Mechanisms of Old and New Cardiotoxic Drugs in Cancer Patients - Alessandra Cuomo (Radcliffe Medical Media, 2019)
Although there have been many improvements in prognosis for patients with cancer, anticancer therapies are burdened by the risk of cardiovascular toxicity. Heart failure is one of the most dramatic clinical expressions of cardiotoxicity, and it may occur acutely or appear years after treatment. This article reviews the main mechanisms and clinical presentations of left ventricular dysfunction induced by some old and new cardiotoxic drugs in cancer patients, referring to the most recent advances in the field. The authors describe the mechanisms of cardiotoxicity induced by anthracyclines, which can lead to cardiovascular problems in up to 48% of patients who take them. The authors also describe mechanisms of cardiotoxicity induced by biological drugs that produce left ventricular dysfunction through secondary mechanisms. They outline the recent advances in immunotherapies, which have revolutionised anticancer therapies.